Energy consumption characterization in precision hard machining using CBN cutting tools. Issue 9 (August 2016) - Grzesik, Wit; Denkena, Berend; Żak, Krzysztof; Grove, Thilo; Bergmann, Benjamin
Abstract In this paper, the contribution of tool wear to the energy balance was determined for precision hard turning using chamfered CBN cutting tools. The tool nose wear VBC and the corresponding changes of component forcesF c, F f andF p resulting from tool wear evolution were continuously measured during wear tests. Based on the cutting mechanics, specific cutting and ploughing energies were calculated for a number of tool wear states. In particular, changes of energy balance due to tool wear under variable feed rate, depth of cut and tool nose radius were discussed. A distinction between material removal conditions resulting from precision cutting and grinding at a very low uncut chip thickness is considered.